Encoding the Sequence of Specific Autoantibodies Against beta-Amyloid and alpha-Synuclein in Neurodegenerative Diseases - Albus, Alexandra; Jördens, Marit; Möller, Moritz; Dodel, Richard (Frontiers in Immunology, 2019)
There is no effective disease-modifying therapy for Alzheimer’s and Parkinson’s Disease. As pathological hallmarks, the specific proteins Amyloid-β and α-Synuclein aggregate, deposit and destabilize neurons, which lead to their degeneration. In the context of a potential immunization strategy for these diseases, naturally occurring autoantibodies could play a crucial role due to their ability to inhibit protein aggregation and to mediate their phagocytosis. We developed a procedure to extract the genetic information of these Amyloid-β- and α-Synuclein- specific naturally occurring autoantibodies for future passive immunization strategies. We performed FACS-based single-cell sorts from healthy whole-blood donations and performed single-cell RT-PCR studies to duplicate the coding sequences of antigen-binding regions of each antibody-secreting B1 cell. Sequences were further analyzed to determine the CDR sequences and the germline expression. Thereby, only low percentages of B1 cells were Amyloid-β+/α-Synuclein+. After cell sorting the variable regions of full IgGs were sequenced. Thereby, the sequence analysis demonstrated a preferred usage of IGVH3 and IGKV1. The study we present here describes a way to extract and duplicate the sequence information of autoantibodies based on single blood donations and to produce a recombinant antibody pool for a potential passive immunization against neurodegenerative diseases. We sorted a small pool of CD20+ CD27+ CD43+ CD69- IgG+ and Aβ+/α-Syn+ B cells.